Confiabilidad Y Baremos Del Cuestionario De Características Psicológicas Relacionadas Al Rendimiento (Cprd) Deportivo En Árbitros De Fútbol (2015)
The referee football is a sport that must perform at their best as an athlete performance when running his arbitration work, this performance is generated in a stressful scenario of sporting competition, this performance requirement demand the most of their psychological skills as any other athlete, why refereeing errors occur frequently. This degree work was to determine the values of reliability and normative data Psychological Characteristics Questionnaire Related to Sports Performance (CPRD) in Football Referees. Study of quantitative approach, no experimental design, cross-section and instrumental range. The instrument reliability was calculated through the internal consistency index is Cronbach's alpha of .88. General scales were designed for each of the factors of the questionnaire. The scales of motivation, team building and mental ability should be reviewed, particularly the skill level; no significant differences between central referees and assistants were identified. In conclusion, the questionnaire is global because it allows an objective measure of psychological skills in football referees.